Islamic Verse-Making in African Societies: Themes, Forms, Functions - Brigaglia, Andrea (Journal for Islamic Studies, 2023)
The present volume of the Journal for Islamic Studies is born out of a series of exchanges between the editor and the authors over the last few years. These exchanges realized the need for a comparative perspective on the study of Islamic religious verse in Africa, across the boundaries of languages (Arabic, Hausa, Somali, Swahili, etc.), regions (East Africa, West Africa, etc.) and themes (mystical poetry, didactic poetry, political poetry, etc.). In 1996, a cross-cultural perspective on the study of Islam and poetry had been inaugurated by Stefan Sperl and Christopher Shackle’s two-volume collection on Islamic poetry in Africa and Asia.1 Five years later, Martin Orwin and Farouk Topan had taken up the challenge by editing an important special issue of the Journal of African Cultural Studies on Islamic poetry in Africa.2 Since then, separate research on selected regional traditions (the Horn; the Swahili coast; the Western and Central Sudan) or themes (praise poetry; devotional poetry; invective poetry; Jihadi songs) has grown enough to make a comparative perspective more necessary, and potentially more compelling, than before.